Secretagogin is expressed in sensory CGRP neurons and in spinal cord of mouse and complements other calcium-binding proteins, with a note on rat and human - Shi Tie-Jun Sten; Xiang Qiong; Zhang Ming-Dong; Tortoriello Giuseppe; Hammarberg Henrik; Mulder Jan; Fried Kaj; Wagner Ludwig; Josephson Anna; Uhlén Mathias; Harkany Tibor; Hökfelt Tomas (SAGE Publishing, 2012)
Abstract Background Secretagogin (Scgn), a member of the EF-hand calcium-binding protein (CaBP) superfamily, has recently been found in subsets of developing and adult neurons. Here, we have analyzed the expression of Scgn in dorsal root ganglia (DRGs) and trigeminal ganglia (TGs), and in spinal cord of mouse at the mRNA and protein levels, and in comparison to the well-known CaBPs, calbindin D-28k, parvalbumin and calretinin. Rat DRGs, TGs and spinal cord, as well as human DRGs and spinal cord were used to reveal phylogenetic variations. Results We found Scgn mRNA expressed in mouse and human DRGs and in mouse ventral spinal cord. Our immunohistochemical data showed a complementary distribution of Scgn and the three CaBPs in mouse DRG neurons and spinal cord. Scgn was expressed in ~7% of all mouse DRG neuron profiles, mainly small ones and almost exclusively co-localized with calcitonin gene-related peptide (CGRP). This co-localization was also seen in human, but not in rat DRGs. Scgn could be detected in the mouse sciatic nerve and accumulated proximal to its constriction. In mouse spinal cord, Scgn-positive neuronal cell bodies and fibers were found in gray matter, especially in the dorsal horn, with particularly high concentrations of fibers in the superficial laminae, as well as in cell bodies in inner lamina II and in some other laminae. A dense Scgn-positive fiber network and some small cell bodies were also found in the superficial dorsal horn of humans. In the ventral horn, a small number of neurons were Scgn-positive in mouse but not rat, confirming mRNA distribution. Both in mouse and rat, a subset of TG neurons contained Scgn. Dorsal rhizotomy strongly reduced Scgn fiber staining in the dorsal horn. Peripheral axotomy did not clearly affect Scgn expression in DRGs, dorsal horn or ventral horn neurons in mouse. Conclusions Scgn is a CaBP expressed in a subpopulation of nociceptive DRG neurons and their processes in the dorsal horn of mouse, human and rat, the former two co-expressing CGRP, as well as in dorsal horn neurons in all three species. Functional implications of these findings include the cellular refinement of sensory information, in particular during the processing of pain.